Comparative analysis of T-Beam along with deck slab by Courbon's method and STAAD. Pro. (2022) - Zain, Mohd.; Kumar Pandey, Ashwani; Varma, Rakesh; Kumar Srivastava, Ranjendra
Abstract: Bridge design is crucial since it entails a great deal of exertion in terms of analysing loads and load distribution on structural components. The software STAAD. ProV8i version was used to analyses a simple T-beam bridge using IRC loadings and the logical method approach. The main aim is to study the T-beam of the bridge, as well as the deck slab, using Courbon's method and calculating the values of bending moment, shear force, and deflection for a span range of 18.25 m, and to compare the manual results with those obtained using the programme STAAD. ProV8i. And we found that the designing by software was more economical as compared with manual design.